P061 INFLAMMATORY BOWEL DISEASE SEVERITY INFLUENCES VITAMIN D MONITORING. (18th January 2018) - Dave, Jenny; Fairfield, Bradley; Alsulaimi, Najwan; Almedimigh, Abdulaziz; Borum, Marie L
Abstract: It has been suggested that vitamin D has a role in the pathogenesis and regulation of inflammatory bowel disease (IBD). However, physicians inconsistently obtain vitamin D levels in IBD patients for unclear reasons. It is speculated that the severity of the disease may influence physicians' vitamin D testing. This study evaluated whether the frequency of vitamin D assessments occurred more often in patients maintained on biologic (BIO) and/or immunosuppressants (IM) therapy compared to aminosalicylates (ASA). A chart review of consecutive IBD patients at a university gastroenterology practice during a 6 month period was performed. Patient age, gender, ethnicity and medication regimens were obtained. Vitamin D levels within the past year were noted. Analysis was performed using Fisher Exact test with significance set at p<0.05. This study was approved by the IRB. Records of 268 patients (118 men, 150 women; mean age 43; 158 Crohn's, 109 ulcerative colitis, 1 indeterminate colitis) were reviewed. In the 207 (77.24%) patients with vitamin D levels, 84 were on a BIO +/- IM and 93 were on an ASA alone. There was a significant difference (p=0.0118) in the rate at which patients on BIO +/- IM (104/138; 81.25%) were tested compared to those on ASA (61/93; 65.59%). There was no significant difference (p=0.5846) in the rates of vitamin D deficiency between the two groups. This study suggests that the severity of IBD may influence vitamin D monitoring, since IBD patients on BIO +/- IM had more frequent vitamin D levels obtained. Notably, the rate of deficiency between those on BIO +/- IM and ASA was not significantly different. While this study is limited due to sample size and single institutional design, it provides insight about physicians' management. Increased efforts to obtain vitamin D level in all IBD patients should occur. Additional research is needed to determine all factors, including severity of disease, that influence vitamin D monitoring in IBD.